The short-term improvements of enriched environment in behaviors and pathological changes of APP/PS1 mice via regulating cytokines - Yuwei Zhang; Ge Wang; Lin Wang; Jian Zhao; Rui Huang; Qianying Xiong (Taylor & Francis Group, 2018)
Objective: To study the effect of enriched environment (EE) on cognitive function and pathological changes in Alzheimer's disease (AD) mice. Method: 6-month-old of the male mice were divided into 3 groups (n = 8), the wild type C57BL/6 mice in the control group, the APP/PS1 transgenic mice of AD reared in either the standard environment or the EE. Mice were feeding for 8 weeks, and then moved into standard environment. The activity and cognitive function were measured by Open-field test and Morris-water Maze. Immunofluorescence was used to detect Aβ plaque, hydroxylamine colorimetric assay was used to detect the activity of Ach, ChAT and AchE, and ELISA was used to detect the Aβ protein and the inflammatory factors IL-1β, IL-6, TNF-α and IFN-γ in serum, as well as the trophic cytokines BDNF, NGF and IGF-1 in hippocampus. Result: Compared with the controls, the behaviors of AD mice were degraded, the Aβ deposition could be detected in the brain, the activity of Ach and ChAT decreased while the AchE increased, and the inflammatory factors increased significantly in serum while the trophic factors decreased in hippocampus. By means of rearing in EE, the activity and cognitive functions of AD mice were improved, and the Aβ plaques were significantly reduced. Meanwhile, the inflammatory factors in serum were reduced while the trophic cytokines increased. Besides, the cholinergic system in the brain were improved without statistic difference. However, 3 months later, these improvements in AD mice which were previously raised in EE disappeared. Conclusion: The EE can improve the behaviors of AD mice, reduce the Aβ deposition in the brain, regulate the levels of cytokines, and have benefit in pathological changes in AD, but these improvements are short-term.